An Analysis of Cash Basis Accounting in Consignment Reseller Operations on Marketplace Platforms: A Case Study of Zaril Company: ANALISIS PENCATATAN KEUANGAN CASH BASIS PADA KEGIATAN RESELLER SISTEM KONSINYASI DI MARKETPLACE: STUDI KASUS PADA ZARIL COMPANY - Akbar Maulana; Fitri Komariyah (Green Engineering Society, 2026)
Abstract. This study aims to analyze cash-basis financial recording practices in reseller businesses that operate under a consignment system on marketplace platforms, focusing on a case study of Zaril Company. A qualitative approach with a case study method was employed. Data were collected through interviews, observations, and documentation involving resellers engaged in marketplace sales activities. Data analysis was conducted descriptively by comparing the existing recording practices with accounting theories related to cash-basis accounting and consignment transactions. The findings indicate that resellers have implemented cash-basis accounting by recognizing revenue when payment is received. However, the records remain simple and are not yet capable of providing accurate financial information. Resellers only record sales transactions without clearly distinguishing revenue, expenses, and profit. Furthermore, in the context of consignment transactions, revenue recognition has not fully complied with accounting principles, which require revenue to be recognized based on the margin or commission earned. These findings highlight the need to improve financial recording practices and accounting understanding to produce more relevant and reliable financial information. Abstrak. Penelitian ini bertujuan menganalisis pencatatan keuangan berbasis cash basis pada praktik reseller yang menggunakan sistem konsinyasi di marketplace dengan studi kasus pada Zaril Company. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus. Data diperoleh melalui wawancara, observasi, dan dokumentasi terhadap reseller yang melakukan aktivitas penjualan melalui marketplace. Analisis data dilakukan secara deskriptif dengan membandingkan praktik pencatatan yang diterapkan dengan teori akuntansi mengenai cash basis dan konsinyasi. Hasil penelitian menunjukkan bahwa reseller telah menerapkan pencatatan cash basis dengan mengakui pendapatan saat pembayaran diterima. Namun, pencatatan yang dilakukan masih sederhana dan belum mampu menyajikan informasi keuangan secara akurat. Reseller hanya mencatat transaksi penjualan tanpa memisahkan pendapatan, biaya, dan keuntungan secara jelas. Selain itu, dalam sistem konsinyasi, pengakuan pendapatan belum sepenuhnya sesuai dengan prinsip akuntansi yang mengharuskan pendapatan diakui berdasarkan margin atau komisi yang diperoleh. Temuan ini menunjukkan perlunya peningkatan pemahaman dan pengelolaan pencatatan keuangan agar informasi yang dihasilkan lebih relevan dan andal